REGENERATIVE MEDICINE IN BURN INJURY: A BIBLIOMETRIC ANALYSIS AND LITERATURE REVIEW - Rahman, Naufal Aminur; Devina, Santi; Pradana, Muhammad Yusuf Billiant; Godwin Emeka Ozokolie; Lanre Peter Daodu; Shreya Pandey (Universitas Airlangga, 2024)
Highlights: This research analyzes regenerative medicine trends for burn injuries, providing valuable insights into focal points and article characteristics, enhancing understanding of this critical healthcare issue. This research analyzes trends in regenerative medicine for burn injuries, highlighting emerging areas like 3D printing, nanotechnology, and photothermal therapy as promising future research directions. Abstract: Introduction: Burn injuries represent a significant global health concern, demanding effective management strategies to mitigate their impact. Regenerative medicine offers promising approaches to address burn injury management, utilizing innovative techniques to improve wound healing and tissue regeneration. This paper presents a comprehensive bibliometric analysis and literature review, highlighting trends, hotspots, and article profiles in the application of regenerative medicine for burn injury management, offering valuable insights for future research to enhance burn care. Methods: A Scopus database search spanning from 2004 to 2024 was conducted using keywords related to regenerative medicine, burn injuries, and wound healing, yielding 602 relevant documents for analysis. Subsequent bibliometric analysis using VOSviewer and Biblioshiny identified key trends and contributors in the field. Results: The results indicate an increase in research studies over the years, peaking in 2022, followed by a slight decline. Zhang Y emerged as the top researcher, with the United States leading in research output. Researchers primarily focused on four main areas: materials and techniques, injury management, cell-based therapies, and wound healing strategies. Emerging areas such as 3D printing, nanotechnology, and photothermal therapy are gaining interest for future research. Conclusion: This study provides valuable insights into the evolving landscape of regenerative medicine for burn injury management. Zhang Y's significant contributions and the United States' leading role underscore the global effort in advancing research in this area. The exploration of new technologies like 3D printing and nanotechnology, alongside traditional approaches, signifies the dynamic nature of biomedical research in addressing burn injuries.